PANDANGAN PIHAK KUA KASIHAN, BANTUL, YOGYAKARTA TENTANG KAWIN HAMIL - Dian Andromeda Yustika (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2014)
Intercourse is performed in the absence of legal marriage is called fornication. Committed adultery often leads to pregnancy . Marriage in the state of pregnant women have become pregnant as a result of adultery called mating. KUA, as the institution of marriage registrar, shall note any marriage, including marital pregnant women due to adultery. KUA Kasihan, Bantul notes that pregnant women due to adultery marriage is allowed, but only with men who impregnate. The reason is for the benefit of the child and the child’s status nasab. The reference is to Article 53 KHI and does not conflict with the contents of Surah an -Nur verse 3 This is an application of the theory of welfare and maqashid ash- Shari’ah. Marriage of pregnant women with men who did not impregnate can not be implemented, because madharatnya greater than maslahatnya, namely aduknya mixed descent. This paper examines how the KUA opinion about marriage pregnant, including the basis and reasons used in pregnant women due to marry adultery is in KUA Kasihan, Bantul.